Genetic Loci Associated with Salt Tolerance in Advanced Breeding Populations of Tetraploid Alfalfa Using Genome‐Wide Association Studies. Issue 1 (1st March 2019) - Liu, Xiang‐Ping; Hawkins, Charles; Peel, Michael D.; Yu, Long‐Xi
Abstract : Many agricultural lands in the western United States consist of soil with high concentrations of salt, which is detrimental to alfalfa ( Medicago sativa L.) growth and production, especially in the region where water resource is limited. Developing alfalfa varieties with salt tolerance is imperative for sustainable production under increasing soil salinity. In the present study, we used advanced alfalfa breeding populations and evaluated five traits related to salt tolerance including biomass dry weight (DW) and fresh weight (FW), plant height (PH), leaf relative water content (RWC), and stomatal conductance (SC) under control and salt stress. Stress susceptibility index (SSI) of each trait and single‐nucleotide polymorphism (SNP) markers generated by genotyping‐by‐sequencing (GBS) were used for genome‐wide association studies (GWAS) to identify loci associated with salt tolerance. A total of 53 significant SNPs associated with salt tolerance were identified and they were located at 49 loci through eight chromosomes. A Basic Local Alignment Search Tool (BLAST) search of the regions surrounding the SNPs revealed 21 putative candidate genes associated with salt tolerance. The genetic architecture for traits related to salt tolerance characterized in this report could help in understanding the genetic mechanism by which salt stress affects plant growth and production in alfalfa. The markers and candidate genes identified in the present study would be useful for marker‐assisted selection (MAS) in breeding salt‐tolerant alfalfa after validation of the markers.